Suicide prevention strategies revisited: 10-year systematic review - Zalsman, G; Hawton, K; Wasserman, D; van Heeringen, K; Arensman, E; Sarchiapone, M; Carli, V; Höschl, C; Barzilay, R; Balazs, J; Purebl, G; Kahn, J; et al. (Elsevier, 2016)
Many countries are developing suicide prevention strategies for which up-to-date, high-quality evidence is required. We present updated evidence for the effectiveness of suicide prevention interventions since 2005.We searched PubMed and the Cochrane Library using multiple terms related to suicide prevention for studies published between Jan 1, 2005, and Dec 31, 2014. We assessed seven interventions: public and physician education, media strategies, screening, restricting access to suicide means, treatments, and internet or hotline support. Data were extracted on primary outcomes of interest, namely suicidal behaviour (suicide, attempt, or ideation), and intermediate or secondary outcomes (treatment-seeking, identification of at-risk individuals, antidepressant prescription or use rates, or referrals). 18 suicide prevention experts from 13 European countries reviewed all articles and rated the strength of evidence using the Oxford criteria. Because the heterogeneity of populations and methodology did not permit formal meta-analysis, we present a narrative analysis.We identified 1797 studies, including 23 systematic reviews, 12 meta-analyses, 40 randomised controlled trials (RCTs), 67 cohort trials, and 22 ecological or population-based investigations. Evidence for restricting access to lethal means in prevention of suicide has strengthened since 2005, especially with regard to control of analgesics (overall decrease of 43% since 2005) and hot-spots for suicide by jumping (reduction of 86% since 2005, 79% to 91%). School-based awareness programmes have been shown to reduce suicide attempts (odds ratio [OR] 0·45, 95% CI 0·24-0·85; p=0·014) and suicidal ideation (0·5, 0·27-0·92; p=0·025). The anti-suicidal effects of clozapine and lithium have been substantiated, but might be less specific than previously thought. Effective pharmacological and psychological treatments of depression are important in prevention. Insufficient evidence exists to assess the possible benefits for suicide prevention of screening in primary care, in general public education and media guidelines. Other approaches that need further investigation include gatekeeper training, education of physicians, and internet and helpline support. The paucity of RCTs is a major limitation in the evaluation of preventive interventions.In the quest for effective suicide prevention initiatives, no single strategy clearly stands above the others. Combinations of evidence-based strategies at the individual level and the population level should be assessed with robust research designs.The Expert Platform on Mental Health, Focus on Depression, and the European College of Neuropsychopharmacology.